2007
DOI: 10.1002/jrs.1761
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐enhanced Raman scattering study of the red dye laccaic acid

Abstract: FT-Raman and surface-enhanced Raman scattering (SERS) spectroscopy were applied to the study of lac dye, a highly fluorescent anthraquinone red dye. The SERS spectra were obtained at different pH values, on Ag nanoparticles prepared by chemical reduction with citrate and hydroxylamine, and at several excitation wavelengths, in order to find the best experimental conditions for the detection of the lac dye. The lower detection limit was achieved using nanoparticles prepared by reduction with hydroxylamine, exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 20 publications
(10 reference statements)
3
43
0
Order By: Relevance
“…In particular, wileyonlinelibrary.com/journal/jrs under the present experimental conditions, we observe in all cases the following: -a weak band around 1620 cm −1 , assigned to the stretching mode of the C-C bonds in the rings and of the C O group interacting with the Ag nanoparticles; -a weak band around 1550 cm −1 , which can be attributed again to a ring C-C stretching mode; -a medium band at about 1460-1470 cm −1 , assigned to ring C-C stretching modes and to C-OH bending modes; -a medium-strong band at a wavenumber ranging from 1390 to 1420 cm −1 with a similar assignment; -a strong band at 1290-1295 cm −1 , assigned to C-OH bending modes. [11,12,36] Besides these bands that are common to all the examined dyes, some signals are characteristic of some of them. In detail they are the following:…”
Section: Anthraquinone Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, wileyonlinelibrary.com/journal/jrs under the present experimental conditions, we observe in all cases the following: -a weak band around 1620 cm −1 , assigned to the stretching mode of the C-C bonds in the rings and of the C O group interacting with the Ag nanoparticles; -a weak band around 1550 cm −1 , which can be attributed again to a ring C-C stretching mode; -a medium band at about 1460-1470 cm −1 , assigned to ring C-C stretching modes and to C-OH bending modes; -a medium-strong band at a wavenumber ranging from 1390 to 1420 cm −1 with a similar assignment; -a strong band at 1290-1295 cm −1 , assigned to C-OH bending modes. [11,12,36] Besides these bands that are common to all the examined dyes, some signals are characteristic of some of them. In detail they are the following:…”
Section: Anthraquinone Dyesmentioning
confidence: 99%
“…1(a) and, (b)). [11,12] 3. Cochineal gives rise to two rather intense bands at 732 and 660 cm −1 , the first of which is also reported in the literature [11] with medium intensity, irrespective of the pH value, and assigned to the rocking mode of the methyl group characterising the structure of carminic acid and to the out-ofplane bending modes of C-H and C-OH bonds.…”
Section: Anthraquinone Dyesmentioning
confidence: 99%
“…that provide the best SERS spectra. Most of the studies refer to red and yellow dyestuffs, mainly anthraquinones (AZ, [15,16] purpurin (PUR), [15] carminic acid, [22] laccaic acid [23] ) and flavonoids, [24 -27] respectively, but significant studies of the SERS spectra of curcumin [28] and some alkaloids [29,30] have also been reported. In some of these studies, theoretical predictions of the corresponding spectra, which help in the assignment of the experimental data, were also made.…”
Section: Introductionmentioning
confidence: 99%
“…In some of these studies, theoretical predictions of the corresponding spectra, which help in the assignment of the experimental data, were also made. Different SERS substrates have been employed, mostly silver colloids reduced with citrate, [14,15,17 -19,21 -34] hydroxylamine [16,22,23,28] or borohydride. [33] But other substrates have been tested as well: electrodes, [13,26] Ag-Al 2 O 3 35 , Tollens mirrors, [31,35] vacuum-evaporated silver nano-island films (AgIF), [31,36] e-beam-deposited AgIF, [37] silver films over nanospheres (AgFON), [38] and Ag nanoparticles obtained in situ by laser photoreduction.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the greatest effort in the field of SERS for art and archaeology aimed at the characterization of reference materials, with special attention being paid to natural red colorants: alizarin, purpurin, carminic and laccaic acids, and related anthraquinones have been the subject of several studies in the scientific literature (Shadi et al 2004;Cañamares et al 2004Cañamares et al , 2006aChen et al 2006;Cañamares and Leona 2007;Baran et al 2009;Rambaldi et al 2015). Articles about the detection of flavonoids (Jurasekova et al 2006(Jurasekova et al , 2008(Jurasekova et al , 2012Wang et al 2007;Teslova et al 2007;Cañamares et al 2009;Corredor et al 2009;Mayhew et al 2013), indigoids (Bruni et al 2010;Oakley et al 2012), and dyes belonging to other molecular classes Cañamares et al 2008aCañamares et al , b, 2010Cañamares et al , 2014Fig.…”
Section: Introductionmentioning
confidence: 98%